NIAT VIEWERS MEMILIH VIDEO PROGRAM MATA NAJWA PADA PLATFORM YOUTUBE: DALAM KAJIAN PRODUCT QUALITY DAN BRAND TRUST - Fitriana, Ni'matul Laili; Ikhram W., M. Abdi Dzil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Increasingly sophisticated technology makes all information spread quickly and evenly through the internet, which in this era the internet has become a necessity of everyday life. The objective of this research is to assess the effect of product quality and brand trust on the intention to watch Mata Najwa program video in YouTube Platform. This quantitative explanatory research consists of primary and secondary data. The primary data was obtained from online questionnaires via Google Forms distributed 150 students of Universitas Brawijaya who watch the said video in YouTube as the respondents. The secondary data was gathered from the company and relevant literature. The result of the data analysis performed in Statistical Product and Service Solution (SPSS) 26 indicate that product quality and brand trust positively and significantly influence the intention to watch Mata Najwa program video in YouTube platform.